Silk fibroin carriers with sustained release capacity for treating neurological diseases - Huang, Xinqi; An, Yumei; Yuan, Shengye; Chen, Chen; Shan, Haiyan; Zhang, Mingyang (Frontiers in Pharmacology, 2023)
Neurological diseases such as traumatic brain injury, cerebral ischemia, Parkinson’s, and Alzheimer's disease usually occur in the central and peripheral nervous system and result in nervous dysfunction, such as cognitive impairment and motor dysfunction. Long-term clinical intervention is necessary for neurological diseases where neural stem cell transplantation has made substantial progress. However, many risks remain for cell therapy, such as puncture bleeding, postoperative infection, low transplantation success rate, and tumor formation. Sustained drug delivery, which aims to extend the duration between doses and maintain constant therapeutic levels in plasma or local injection sites, is considered as a feasible option to maximize therapeutic efficacy and minimize the side effects of drugs in the treatment of neurological diseases. Silk fibroin is a natural polymer with good biocompatibility and a useful matrix for sustained delivery as the processing can be tailored for drug loading, release kinetics and stability by changing the process used in the formation and treatment of all format’s material, such as microsphere, gel, coating/film, scaffold/conduit, microneedle. By manipulating the interactions between silk fibroin and different drug molecules, factors, and cells, sustained release may be achieved through diffusion- and degradation-based release mechanisms, which can induce nerve recovery and restore the function of the nervous system in a slow and persistent manner. Based on these desirable properties of silk fibroin as a carrier with sustained release capacity, we discuss the unique aspects of silk fibroin as a sustained drug delivery platform and highlight the role of silk fibroin-based drug delivery materials in various formats in treating neurological disease in recent years.